Perception of the Effectiveness of Stock Market Recommendations in Relation to Their Real Marketability - Keller, Jakub Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The purpose of this paper is to evaluate the effectiveness of stock market recommendations as a factor supporting investment decisions, both in objective and subjective terms. The applicative objectivity of using recommendations is visualized by indicating their real impact on achieving an above‑average return. Subjective utility refers to the perception of recommendations directly by their recipients, including individual investors. For this purpose, a survey was conducted on a group of 564 respondents whose structure is representative of stock market investors in Poland and the results of the survey were verified by conducting statistical analyses (logit models) on the example of selected brokerage houses indicated by investors as the most and least effective in the prediction. The analyses conducted show an ambiguous perception of stock market recommendations by investors. According to investors, the usefulness of stock recommendations issued by individual brokerage houses varies, resulting in different possibilities of generating income using these reports. The responses of respondents to the objective results of investment models using information from stock market recommendations also indicate that individual perceptions of investors’ recommendations do not necessarily translate into their actual usefulness.